Clinical Presentation, Diagnosis and Management of Cryptococcus gattii Cases: Lessons Learned from British Columbia. Issue 1 (2009) - Galanis, Eleni; Hoang, Linda; Kibsey, Pamela; Morshed, Muhammad; Phillips, Peter
Abstract : The environmental fungus Cryptococcus gattii emerged on Vancouver Island, British Columbia (BC), in 1999. By the end of 2006, it led to 176 cases and eight deaths – one of the highest burdens of C gattii disease worldwide. The present paper describes three cases, and the BC experience in the diagnosis and management of this infection. All three cases presented with pulmonary findings, including cryptococcomas and infiltrates. One also presented with brain cryptococcomas. Cases were diagnosed by chest and brain imaging, and laboratory evidence including serum or cerebrospinal fluid cryptococcal antigen detection and culture of respiratory or cerebrospinal fluid specimens. Genotyping of fungal isolates confirmed infection with C gattii VGIIa. Pulmonary cases were treated with fluconazole. One patient with central nervous system disease was treated with amphotericin B followed by fluconazole. Although this infection remains rare, clinicians should be aware of it in patients with a compatible clinical presentation who are either living in or returning from a trip to BC.